The efficacy and safety of intra-articular injection of corticosteroids in multimodal analgesic cocktails in total knee arthroplasty—a historically controlled study - Wang, Yixiong; Li, Zhichang; Gao, Xuan; Lin, Jianhao (Frontiers in Surgery, 2024)
Total knee arthroplasty (TKA) is common and effective. Optimizing pain control and reducing postoperative discomfort is required for patient satisfaction. No studies have examined the safety and efficacy of intra-articular corticosteroid injections following TKA. This study examines the safety and efficacy of corticosteroids in intra-articular multimodal analgesic injections.This was a historically controlled study at a single academic institution. Before May 2019, during surgery, patients received intraarticular cocktail injection which did not contain corticosteroids, as the non-corticosteroid (NC) group. After June 2019, intraoperatively, patients received intraarticular cocktail injection containing corticosteroids, as the corticosteroid (C) group. Finally, there were 738 patients evaluated, 370 in the C cohort and 368 in the NC cohort. The mean follow-up duration was 30.4 months for the C group and 48.4 months for the NC group.The mean VAS at rest on postoperative day (POD)1 (2.35) and POD 3 (3.88) were significantly lower in the C group, compared with those in the NC group, which were 2.86 (POD1) and 5.26 (POD3) (p<0.05). Walking pain in the C group (4.42) was also significantly lower than that (5.96) in the NC group on POD3 (p<0.05). Patients in the C group had a significantly higher mean ROM (92.55) at POD3 than that (86.38) in the NC group. The mean time to straight leg raise for group C (2.77) was significantly shorter than that (3.61) in the NC group (p < 0.05). The C group also had significantly fewer rescue morphine (1.9) and metoclopramide(0.21) uses per patient than the NC group, which were 3.1 and 0.24, respectively. No significant differences in fever or vomiting rates between groups were found. Patients in neither groups developed periporsthetic joint infections or skin necrosis. One patient in the C group suffered from wound dehiscence and the wound healed well after debridement. No patient died or had a re-operation in either groups.This pilot trial found that intraarticular injection of multimodal analgesia (including corticosteroids) reduced initial postoperative pain, increased ROM in the early postoperative days (up to POD3) , and did not increase wound complications or infection rates in approximately 30 months of followup.